Homogeneous deposition precipitation method for synthesis of carbon nanofibre based Cu-ZrO2 catalyst for hydrogenation of CO2 to methanol - Ud Din, I. (2014)
Deposition precipitation method was employed to synthesize carbon nanofiber based Cu-ZrO2 catalyst (Cu-ZrO2/CNF). Carbon nanofibre of herringbone type was used as a catalyst support. Prior deposition of catalyst particles, carbon nanofibre was oxidized to (CNF-O) with nitric acid solution. Catalyst was characterized by X-ray diffraction (XRD), Fourier Transmission Infrared (FTIR), Transmission Electron Microscopy (TEM) and Temperature-Programmed Reduction (TPR). Highly loaded, well-dispersed and thermally stable catalyst particles with average size of 4 nm were obtained by deposition precipitation method. Reaction studies confirmed the activity of the catalyst towards methanol formation. Â© (2014) Trans Tech Publications, Switzerland.